2006
DOI: 10.12944/cwe.6.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of phytoplankton and artemia in the solar salterns at Tuticorin

Abstract: Salt pan ecosystem of Tuticorin was studied for the distribution of Phytoplankton in two condenser ponds in a particular station, where artemia population was very high. This was monitored for one year in two ponds. Physico chemical parameters were also studied. The population of Bacillariophyceae dominated during monsoon season. Chlorophyceae was high during summer. Phytoplankton density was correlated with artemia population. Artemia biomass was at a maximum during monsoon when the species The occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The previous literature survey revealed that the nanoparticle synthesis using biological sources like algae has been unexplored and unexploited [1][2][3][4][5][6][7][8][9][10][11]. Nanosilver (silver nanoparticle, AgNP) material has a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature survey revealed that the nanoparticle synthesis using biological sources like algae has been unexplored and unexploited [1][2][3][4][5][6][7][8][9][10][11]. Nanosilver (silver nanoparticle, AgNP) material has a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical properties, population analysis and size variation observed in the present study was similar to Shaikha Al Dhaheri & Anitha Saji (2013). Radhika et al (2011) studied the physicochemical and population analysis in Tuticorin environment and noticed the similar kind of results. In the present study, the reported physicochemical parameters are within the normal range but Al Dhaheri (2004) reported Artemia can tolerate and survive up to 237 ppt of salinity.…”
Section: Discussionmentioning
confidence: 61%
“…The natural seawater brought into saltworks also brings with it inorganic nutrients and several marine organisms, which establish stable populations at different salinity levels in saltworks ponds. Among the organisms described in saltworks include phytoplankton (Dolapsakis et al, 2005;Elloumi et al, 2009;Evagelopoulos et al, 2009;Radhika et al, 2011;Chatchawan et al, 2011;Madkour and Gaballah, 2012;Devi et al, 2019), ciliates (Elloumi et al, 2006), halophilic bacteria and archaea (Casamayor et al, 2002;Oren, 2008), zooplankton (Mustafa et al, 1999), as well as macrobenthic invertebrates (Evagelopoulos et al, 2009) and the brine shrimp (Elloumi et al, 2009;Mohebbi, 2010). The consensus from most studies is that species richness, evenness and diversity declines with increasing salinity (Evagelopoulos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, phytoplankton density and biomass have been reported to be highest in the high salinity ponds. Ciliates and most zooplankton except Artemia have shown a decreasing trend with increasing salinity in most studies (Elloumi et al, 2006;Radhika et al, 2011). The wide range of planktonic and benthic communities of marine organisms that develop along the salinity gradient constitute a biological system that plays an important role in the production of high-quality salt through preventing leakage of brine, improving solar energy absorption and water evaporation (Madkour and Gaballah, 2012).…”
Section: Introductionmentioning
confidence: 99%